Towards a sustainable, and economic production future: Proposing a new process for methanol production based on renewable hydrogen. (20th February 2023) - Wei, Haoran; Su, Chenqing; Dai, Jie; Albdeiri, Mahmood Shaker; Alsenani, Theyab R.; Elattar, Samia; Abed, Ahmed M.; Hua, Yinhai
Abstract: Moving towards a sustainable future requires modernized and economic energy production, especially in the context of current policy incentives. In the present paper, a new integrated process using flue gas leaving a power plant is projected and studied. The proposed process consists of a carbon dioxide (CO2 ) capture unit (CCU), a water electrolyzer unit (WEU) for renewable hydrogen production, a power generation unit (PGU), a heat generation unit (HGU), and a methanol production unit (MPU). The designed structure has low CO2 emission, low production cost, and high thermodynamic efficiency. This process is simulated using Aspen HYSYS. The simulation results show that the methanol production in this process is equal to 606, 228 ton/year (methanol with a purity above 99% mole), and according to the environmental analysis, the intensity of CO2 emission is 0.61 k g C O 2 k g M e O H, which is lower compared to that of bi- and tr-reforming processes. The results indicate that the overall exergy and energy efficiencies of the proposed process are 71.97% and 56.74%, respectively. Thermodynamic analysis determines that the exergy destruction intensity of this process is equal to 29.54 M J k g M e O H, and the highest destruction happens in the CCU (62.38%). It is also found that the exergy efficiency of the CCU, MPU, WEU, HGU, and PGU is 97%, 92%, 93%, 48%, and 53%, respectively. The exergy analysis exhibits that the coefficient of effectiveness ( ψ i ) in the CCU is high (equals 85.89%), so it is the main factor in increasing the second law efficiency of the proposed process. Finally, according to the economic analysis, it is determined that the total annual cost and the total production cost of methanol in the presented structure respectively are 31, 479, 267 $ and 0.52 $ k g M e O H, which compared to similar technologies based on renewable energy is lower by 64.86%. It is suggested to use this sustainable production mode to promote economic production in some pilot projects or high-tech parks. Highlights: A novel integrated process for methanol production using renewable hydrogen. Process simulation by Aspen HYSYS and 4E analysis. High thermodynamic efficiencies, low CO2 emission, and low production cost. Overall exergy and energy efficiencies of the proposed process are 71.97% and 56.74%. Total annual cost and the methanol production cost are 31.47 M$ and 0.52 $ k g M e O H